Scheduling Algoritma di Sistem Operasi Real-Time - Arie Miftah Budiman; Moh. Restu Nur Rizki; Ridwan Ahri; Rafi Suswidia; Abdul Halim Anshor (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
Real-time operating systems (RTOS) are critical components in various applications requiring rapid response times and high precision, such as in the automotive, medical, and telecommunications industries. Scheduling algorithms in these systems function to allocate CPU time for task execution according to priority, ensuring each task is completed before its deadline. This study aims to evaluate key algorithms, such as Rate Monotonic Scheduling (RMS), Earliest Deadline First (EDF), and heuristic-based algorithms, to identify the most effective method in meeting real-time system requirements. Based on literature analysis, RMS and EDF each exhibit advantages in specific scenarios, while hybrid algorithms show potential for further development.